Success and failure factors in ventilator weaning protocols: What the scientific evidence says (Research, Society and Development, 2026)
This study aimed to analyze, based on current scientific evidence, the main factors associated with the success and failure of ventilator weaning protocols in critically ill patients. To this end, a literature review was conducted using the PubMed, PEDro, SciELO, and Cochrane databases, employing descriptors related to ventilator weaning. Studies published between 2018 and 2025, with robust methodology and full-text availability, were included. Data were organized and analyzed descriptively. The results showed that strict clinical criteria and the spontaneous breathing trial are fundamental methods for assessing readiness for extubation. Successful extubation depends on clinical stability, adequate gas exchange, muscle strength, and the ability to protect the airways. Failure is associated with prolonged mechanical ventilation, increased incidence of pneumonia, and higher mortality. The role of physiotherapy proves to be decisive in the extubation process. Post-extubation strategies, such as noninvasive ventilation and high-flow oxygen therapy, have demonstrated effectiveness in preventing reintubation and improving clinical outcomes, especially in high-risk patients. Therefore, it is concluded that ventilator weaning requires a careful and continuous assessment, with the physiotherapist as one of the main professionals involved, and that its success depends on multiple factors.